2010
DOI: 10.1016/j.jpowsour.2010.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of extra low interstitials ferritic stainless steels for bipolar plates of proton exchange membrane fuel cells

Abstract: Ferritic stainless steels can be attractive bipolar plate materials of proton exchange membrane fuel cell (PEMFC), provided that the stainless steels show sufficient corrosion resistance, for instance, by eliminating interstitial elements such as carbon and nitrogen. In the present study, thus, ferritic stainless steels (19Cr2Mo and 22Cr2Mo) with extra low interstitials (ELI) are evaluated to determine demanded level of chromium content to apply them for PEMFC bipolar plates. In a simulated PEMFC stainless ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Ferritic stainless steels also have been considered as possible bipolar plate material; but, initially their ICR and corrosion resistant properties have been reported to be inferior to those of austenitic stainless steels [71]. More recently, however, it has been reported that the inclusion of small amounts of chromium can substantially improve the corrosion resistance of such plates in simulated and real PEMFC environments [72]. Kumagai et al [72] conducted a series of experiments on ferritic stainless steel plates in simulated and real PEMFC environments.…”
Section: Bare Metals As Bipolar Platesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferritic stainless steels also have been considered as possible bipolar plate material; but, initially their ICR and corrosion resistant properties have been reported to be inferior to those of austenitic stainless steels [71]. More recently, however, it has been reported that the inclusion of small amounts of chromium can substantially improve the corrosion resistance of such plates in simulated and real PEMFC environments [72]. Kumagai et al [72] conducted a series of experiments on ferritic stainless steel plates in simulated and real PEMFC environments.…”
Section: Bare Metals As Bipolar Platesmentioning
confidence: 99%
“…More recently, however, it has been reported that the inclusion of small amounts of chromium can substantially improve the corrosion resistance of such plates in simulated and real PEMFC environments [72]. Kumagai et al [72] conducted a series of experiments on ferritic stainless steel plates in simulated and real PEMFC environments. It was reported that by reducing the amounts of carbon and nitrogen and maintaining a minimum of 22 wt% chromium in the ferritic stainless steel plates, comparable performance in terms of corrosion resistance and ICR is observed.…”
Section: Bare Metals As Bipolar Platesmentioning
confidence: 99%